PENGARUH PENGATURAN FILL DENSITY TERHADAP SIFAT MEKANIS POLYLACTIC ACID HASIL TEKNOLOGI FUSED DEPOSITITION MODELLING - Braam Delfian Prihadianto; Suryo Darmo; Radhian Krisnaputra (Jurnal Teknologi Terpadu, 2022)
Along with advances in science and technology in creative industry, the production process no longer relies on manual creativity, but develops and expands the application of technology to simplify and accelerate the production process. One example of the creative industry sector that applies technological developments is the miniature industry. A new technology that is starting to be in demand among miniature manufacturers is the Fused Depositition Modeling (FDM) technology. It is a method using solid base rapid prototyping technology with an extrusion process and is a solution to the above problems. Polylactic Acid (PLA) is one of the materials used by miniature manufacturers, because this material is included in the aliphatic polyester group which is made from α-hydroxy acid and has degraded properties, making this material relatively safer for health and the environment. The research focuses on the mechanical properties of FDM technology with PLA filament materials, especially tensile and bending strength. This study used an experimental method with reference to the FDM machining parameters with a variation of the fill density from 0.1 to 1.0. Based on the results of experiments and tests that have been done, the tensile strength values are 29.063 - 36.215 MPa and the bending strengths are between 42.520 - 80.315 MPa. Therefore based on the test results it can be concluded that the fill density parameter affects the tensile and bending strengths produced by FDM technology with PLA material.